2016
DOI: 10.13189/eer.2016.040203
|View full text |Cite
|
Sign up to set email alerts
|

Public Management Decisions Related to the Decline of California Deer Populations: A Comparative Management Approach

Abstract: Analysis of data obtained from an ongoing internet search indicates that the U.S. deer harvest has been falling since about the year 2000. California has had the largest decline from peak to recent harvest of any state. Declining timber sales are highly correlated with the decline in California. States like California with a relatively high proportion of public land, a low hunter success rate, and a persistently skewed buck-to-doe harvest ratio report a lower harvest as a percent of peak. An economic framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Between 1450 and 1900, white‐tailed deer ( Odocoileus virginianus ) and mule deer ( O. hemionus ) populations in what became the U.S.A. declined from an estimated 40+ million individuals to fewer than half a million in 1900 (seeMcCabe & McCabe, ; Webb, and references therein). This largely reflected unregulated commercial and subsistence hunting fuelled by a growing number of settlers.…”
Section: Deer and Wolves From Decline To Recovery: How And Why Did Imentioning
confidence: 99%
“…Between 1450 and 1900, white‐tailed deer ( Odocoileus virginianus ) and mule deer ( O. hemionus ) populations in what became the U.S.A. declined from an estimated 40+ million individuals to fewer than half a million in 1900 (seeMcCabe & McCabe, ; Webb, and references therein). This largely reflected unregulated commercial and subsistence hunting fuelled by a growing number of settlers.…”
Section: Deer and Wolves From Decline To Recovery: How And Why Did Imentioning
confidence: 99%
“…In response, hunting was increasingly regulated from the early 1900s onward in order to manage deer populations ( Mackie, 1987 ; Jensen et al, 2023 ). Webb (2016) noted that the recovery of deer populations in the far western US was faster than for populations of white-tailed deer in the east because surviving deer populations in the early 1900s in the Pacific Coast states were generally higher in numbers (and presumably more geographically widespread within their range). Within the core geographic range of I. pacificus , Jensen et al (2023) suggested that around 1920 there were more than 210,000 deer ( O. hemionus columbianus ) present in the Coast Ranges from northern California to southern British Columbia, together with an unspecified number of deer ( O. hemionus hemionus ) in the Coast Range of southern California and the Sierra Nevada foothills.…”
Section: Association Of Changing Landscapes and Host Populations With...mentioning
confidence: 99%
“…Within the core geographic range of I. pacificus , Jensen et al (2023) suggested that around 1920 there were more than 210,000 deer ( O. hemionus columbianus ) present in the Coast Ranges from northern California to southern British Columbia, together with an unspecified number of deer ( O. hemionus hemionus ) in the Coast Range of southern California and the Sierra Nevada foothills. Deer hunt data from California indicate annual harvests in the range of 25,000 animals in the late 1920s, then steadily rising harvest numbers to a peak of 80,000 to 100,00 animals in some years in the late 1950s, followed by a declining trend from the late 1960s onward ( Longhurst et al, 1976 ; Webb, 2016 ). Moreover, annual estimates of the total deer population in California ( O. hemionus hemionus and O. hemionus columbianus combined) were higher in the late 1950s (range from 1955 to 1959 of 1100,000–1200, 000 deer) than in the late 1990s (range from 1995 to 1999 of 531, 000–752,000 deer) and the late 2010s (range from 2015 to 2019 of 458, 000–637,000 deer) ( Connolly, 1981 ; Jensen et al, 2023 ).…”
Section: Association Of Changing Landscapes and Host Populations With...mentioning
confidence: 99%